The EU and the negotiations for a binding treaty on business and human rights: Multilateral cooperation for strengthening the EU's strategic autonomy in supply chains - Sikho Luthango; Meike Schulze (Stiftung Wissenschaft und Politik (SWP), 2023)
The European Union (EU) is seeking out new partnerships and to strengthen existing ones, particularly with Global South states, to enhance its open strategic autonomy. This includes a resilient supply of raw materials for its twin transition to a digital and green economy. Hosting many transnational corporations, several of these partners advocate for a binding international standard to regulate business and human rights beyond the non-binding United Nations Guiding Principles (UNGPs). Thus, the EU should establish a mandate and actively engage in the negotiations for a Binding Treaty on Business and Human Rights (BHR) to consolidate its image as a defender of human rights internationally. Multilateral negotiations enable dialogue and mutual cooperation that regional and national laws on supply chain due diligence do not, and thus risk acceptance by international partners once implemented. This poses a challenge for mutual cooperation, which is necessary to achieve corporate accountability.
Keywords: 320; supply chains; human rights; environmental rights; United Nations Guiding Principles; UNGP; transnational corporations; TNC; legally binding instrument; LBI; Global Compact; BRICS states; forum non conveniens; rxtraterritorial obligations; ETOs; Corporate Sustainability Due Diligence Directive; CSDDD